2019
DOI: 10.1089/trgh.2018.0068
|View full text |Cite|
|
Sign up to set email alerts
|

Demographic and Behavioral Profiles of Nonbinary and Binary Transgender Youth

Abstract: Purpose: Emerging literature suggests there may be important differences in the demographic characteristics and health profiles of nonbinary transgender youth compared to binary transgender youth.Methods: Between June 2017 and June 2018, 202 transgender youth aged 15–24 years were recruited into a randomized trial of home HIV testing, Project Moxie. This analysis compares demographic and health risk behavior characteristics between youth reporting nonbinary and binary transgender identities in baseline surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Thus, the gender-stratified, transgender subanalysis is only representative of transgender individuals who have accessed gender-affirming hormones or surgery. Notably, across community-based studies, nonbinary individuals have comprised 35% to 42% of transgender samples 6 , 47 , 48 and many nonbinary individuals do not use gender-affirming hormones or procedures 6 , 49 , 50 ; thus, it is likely that most individuals who were excluded from our gender-stratified analyses were nonbinary people who had not accessed hormones or surgery. Furthermore, research finds that TF people are less likely to receive various forms of gender-affirming services than TM people 16 , 51 and nonreceipt of gender-affirming care is associated with substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the gender-stratified, transgender subanalysis is only representative of transgender individuals who have accessed gender-affirming hormones or surgery. Notably, across community-based studies, nonbinary individuals have comprised 35% to 42% of transgender samples 6 , 47 , 48 and many nonbinary individuals do not use gender-affirming hormones or procedures 6 , 49 , 50 ; thus, it is likely that most individuals who were excluded from our gender-stratified analyses were nonbinary people who had not accessed hormones or surgery. Furthermore, research finds that TF people are less likely to receive various forms of gender-affirming services than TM people 16 , 51 and nonreceipt of gender-affirming care is associated with substance use.…”
Section: Discussionmentioning
confidence: 99%
“…First, the participants of The PRIDE study are predominantly non-Latino, White, and highly educated. As research suggests that nearly one third of gender-expansive people are not White, these populations are underrepresented in the present study [ 45 ]. Overall, this may limit the generalizability of these results to people of color.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are within-group differences among TGE youth that may potentiate risk (Rimes et al, 2019). For example, research indicates there are differences in stress levels and life satisfaction for transgender youth compared to non-binary youth (Rimes et al, 2019;Todd et al, 2019). Further, the challenges faced by TGE youth may be complicated by other marginalized aspects of their identities, such as race and/or ethnicity (Atteberry-Ash et al, 2019;Birkett et al, 2015;James et al, 2016;Kosciw et al, 2018).…”
Section: Victimization Among Transgender and Genderexpansive Youthmentioning
confidence: 99%
“…Beyond a lack of sexual health resources, research has indicated that TGE youth generally experience inadequate access to comprehensive physical and mental health services (Mizock & Mueser, 2014). This has frequently been a problem for homeless youth (Hudson et al, 2010), but the difficulties for TGE youth may be compounded by stigma and discrimination and a lack of gender-affirming healthcare providers Todd et al, 2019;Vance et al, 2015). The lack of appropriate care afforded to TGE youth, especially those who are homeless, has been associated with difficulties maintaining overall physical and mental wellbeing (Vance et al, 2015).…”
Section: Transgender and Gender-expansive Youth Homelessness And Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation